1975
DOI: 10.1042/bj1510665
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit collagenase. Immunological identity of the enzymes released from cells and tissues in normal and pathological conditions

Abstract: 1. The immunological cross-reactivity between rabbit collagenases from a variety of normal and pathological sources was examined. The specific antibody raised against collagenase secreted from normal rabbit synovial fibroblasts gave reactions of complete identity with collagenases secreted from fibroblasts derived from rabbit skin, and from synovium from experimentally arthritic rabbits. 2. The rabbit fibroblast collagenase was immunologically identical with collagenases obtained from the organ culture medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1976
1976
1990
1990

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…It has also been suggested that fibroblasts may be involved in the resorption of cartilage collagen that occurs in association with granulation tissue (pannus) formation during experimental arthritis in rats (Cullen, 1972). Fibroblasts isolated from synovium of rabbits with experimental arthritis have been shown to produce a collagenase identical to the collagenase produced by normal rabbit fibroblasts (Werb and Reynolds, 1975). Fibroblasts and lymphocytes are the predominating cells in chronic arthritis induced in the rabbit by injecting a cell-free extract of Group A Streptococci (Stein et a/., 1973).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that fibroblasts may be involved in the resorption of cartilage collagen that occurs in association with granulation tissue (pannus) formation during experimental arthritis in rats (Cullen, 1972). Fibroblasts isolated from synovium of rabbits with experimental arthritis have been shown to produce a collagenase identical to the collagenase produced by normal rabbit fibroblasts (Werb and Reynolds, 1975). Fibroblasts and lymphocytes are the predominating cells in chronic arthritis induced in the rabbit by injecting a cell-free extract of Group A Streptococci (Stein et a/., 1973).…”
Section: Discussionmentioning
confidence: 99%
“…In previous attempts to localize interstitial collagenase associated with neoplasms, antisera had been raised against enzyme from non-neoplastic, mesenchymal cells rather than from neoplastic cells (5,6,(12)(13)(14). These antisera crossreacted with collagenase from tumour explants (15) and tumour extracts (5) but in neither ease was the cellular source of the collagenase clear, as it may have originated from surrounding host fibroblasts rather than from neoplastic cells.…”
Section: Introductionmentioning
confidence: 99%
“…These antisera crossreacted with collagenase from tumour explants (15) and tumour extracts (5) but in neither ease was the cellular source of the collagenase clear, as it may have originated from surrounding host fibroblasts rather than from neoplastic cells.…”
Section: Introductionmentioning
confidence: 99%